Utilização de peixes nativos da Amazônia como biomarcadores na avaliação da qualidade da água de uma área industrial no rio Pará - PA - Brasil - MONTES, Caroline da Silva (Universidade Federal do Pará, 2013)
Indiscriminate dumping of toxic substances impairs and deteriorates the water quality. Fish gills have a large surface area; they remain in close contact with the external environment and are particularly sensitive to changes in water quality, for this reason they are quite relevant for environmental monitoring. This study analyzes the gill structure of the fish species Plagioscion squamossissimus and Lithodoras dorsalis from two different sites located an Amazon estuary. A total of 324 specimens were used, this total 176 were P. squamossissimus and 148 L. dorsalis, removing the second gill arch for histological, ultrastructural and immunohistochemical analyses. The histological changes were analysed semiquantitatively according to the histopathological evaluation. The sampled sites differ regarding the rate of occurrence of altered animals, only site A showed healthy animals, 84% of L. dorsalis and 77% of P. squamossissimus had normal gill structure, with the lamellae lined by simple squamous epithelial, composed of pillar, mucous and chloride cells. However, all the specimens collected in sites B revealed tissue changes in the gill lamellae such as: aneurysm; epithelial lifting; cell proliferation; lamellar fusion and cell hypertrophy, this result was also confirmed by scanning electron microscopy. TUNEL analysis indicated that only animals captured on site B showed apoptotic cells. The presence of injury in gill tissues in the animals captured on site B emphasizes the need for more effective pollution control measures with regards to discarding pollutant loads as well as the need for urban planning in this region.